The New Cooperative Medical Scheme (NCMS) and its implications for access to health care and medical expenditure: Evidence from rural China - Dan Liu; Daniel Tsegai (University of Bonn, Center for Development Research (ZEF), 2011)
The New Cooperative Medical Scheme (NCMS) program was implemented in response to illness-led poverty and poor state of healthcare in rural China. Supported by government subsidy, more and more poor rural households are now enrolled in the NCMS. This paper investigates the impact of the NCMS program on improving health care utilization and reducing medical expenditure with a specific focus on the endeavors to unravel the heterogeneous effects of the program for the different regions and income groups. We utilize the China Health and Nutrition Survey data (CHNS) to provide prolific cross section and longitudinal information. A total sample of 6,293 individuals and 2,058 households are included in the analysis. Propensity score matching method and bounding approach are used to infer the causal effect of NCMS and examine the influence of unobservable factors respectively. Major findings indicate that there is a systematic adverse selection in the NCMS program, both in health- and economic-related aspects. Especially in western regions, households with high ratio of migrant workers are less attracted to the NCMS program. The NCMS program improved medical care utilization for the poor and regionally, western regions benefitted more from the program. The NCMS program also induces a moral hazard problem in western regions.
Keywords: 330; Rural China; health insurance; impact evaluation; propensity score matching; Gesundheitspolitik; Krankenversicherung; Armutspolitik; Wirkungsanalyse; Ländlicher Raum; Gesundheitskosten; China